Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/nano10010074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticles with Different Chemical Nature on the Stability and Rheology of Acrylamide Sodium Acrylate Copolymer/Chromium (III) Acetate Gel for Conformance Control Operations

Abstract: During enhanced oil recovery (EOR), reservoir heterogeneities and fluids distributions promote preferential flow channels formation. Therefore, different types of gels have been proposed to improve swept efficiency on chemical flooding by plugging high permeability zones. The purpose of this article is to evaluate the effect that nanotechnology has on the inhibition of syneresis and the rheological properties of the Acrylamide Sodium Acrylate Copolymer/Chromium (III) Acetate gel system for conformance applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…In this case, the intensity of the band at 370 cm −1 , is similar in the analyzed samples due to the presence of the Mg-O functional group. The results are similar to those reported in the scientific literature [53,[55][56][57].…”
Section: Nanoparticlesupporting
confidence: 92%
“…In this case, the intensity of the band at 370 cm −1 , is similar in the analyzed samples due to the presence of the Mg-O functional group. The results are similar to those reported in the scientific literature [53,[55][56][57].…”
Section: Nanoparticlesupporting
confidence: 92%
“…They concluded that the biopolymer content did not help nanoparticles to reduce the IFT. In addition, a homogenous dispersion of the nanoparticles in the solution and a reduction in the polymer adsorption was observed that can explain the enhancement in the sweep eciency and oil recovery [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are attempts to overcome the critical problems such as material instability and environmental issues caused by Pb-based perovskite, due to which the research on OHP materials is still focused on the solar cell application [ 5 , 6 , 7 ]. In the case of materials instability, particularly, the degradation of OHP materials under electron beam, UV (ultra-violet), and visible light illumination conditions has been reported [ 6 , 7 , 8 , 9 , 10 , 11 ]. C. Xiao, et al had reported the two-steps degradation mechanism such as (1) defect formation caused by irradiation damage and (2) phase transformation induced by electron-beam heating with a high-energy electron beam (5 and 10 kV) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%